(1)-x+2y-1的相反数是( )(2)求多项式2x²-3x-1与x²-3x-2的差.可列出算式( ),可化简为( )(3)2a+3(b-c)=( )(去掉括号)2a-3(b-c)=x²-xy+y²=x²-( )x²-xy+y²=x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 14:14:21
(1)-x+2y-1的相反数是( )(2)求多项式2x²-3x-1与x²-3x-2的差.可列出算式( ),可化简为( )(3)2a+3(b-c)=( )(去掉括号)2a-3(b-c)=x²-xy+y²=x²-( )x²-xy+y²=x
(1)-x+2y-1的相反数是( )
(2)求多项式2x²-3x-1与x²-3x-2的差.可列出算式( ),可化简为( )
(3)2a+3(b-c)=( )(去掉括号)
2a-3(b-c)=
x²-xy+y²=x²-( )
x²-xy+y²=x²+( )
(1)-x+2y-1的相反数是( )(2)求多项式2x²-3x-1与x²-3x-2的差.可列出算式( ),可化简为( )(3)2a+3(b-c)=( )(去掉括号)2a-3(b-c)=x²-xy+y²=x²-( )x²-xy+y²=x
(1)-x+2y-1的相反数是(x-2y+1 )
(2)求多项式2x²-3x-1与x²-3x-2的差.可列出算式(2x²-3x-1-(x²-3x-2) ),可化简为(x²+1 )
(3)2a+3(b-c)=(2a+3b-3c) )(去掉括号)
2a-3(b-c)=2a-3b+3c
x²-xy+y²=x²-( xy-y²)
x²-xy+y²=x²+(-xy+y² )
(1)-x+2y-1的相反数是:-(-x+2y-1)=x-2y+1
(2)求多项式2x²-3x-1与x²-3x-2的差。可列出算式(2x²-3x-1-(x²-3x-2)),可化简为(x²+1 )
(3)2a+3(b-c)=(2a+3b-3c)(去掉括号)
2a-3(b-c)=2a-3b+3c
x²-x...
全部展开
(1)-x+2y-1的相反数是:-(-x+2y-1)=x-2y+1
(2)求多项式2x²-3x-1与x²-3x-2的差。可列出算式(2x²-3x-1-(x²-3x-2)),可化简为(x²+1 )
(3)2a+3(b-c)=(2a+3b-3c)(去掉括号)
2a-3(b-c)=2a-3b+3c
x²-xy+y²=x²-( xy-y²)
x²-xy+y²=x²+(y² -xy)
就这样,哦了O(∩_∩)O
收起
用户覆盖